Nesting of solitary wasps and bees in natural and artificial holes in dead wood in young boreal forest stands. Issue 6 (8th April 2015) - Westerfelt, Per; Widenfalk, Olof; Lindelöw, Åke; Gustafsson, Lena; Weslien, Jan
Abstract: Life history traits of solitary nest provisioning bees and wasps (Aculeata) are characterised by low fecundity and extensive parental care. Therefore, it can be expected that egg‐laying females are demanding in their nest choice. Dead wood in young boreal forest stands in mid‐Sweden were surveyed for holes made by different insect species and the occupancy of solitary bees or wasps in those holes was analysed. Artificial nests consisting of wooden poles with pre‐drilled holes were used for comparison. In 1634 wood objects, 5793 potential nesting holes of 16 types were labelled to insect species or genera that had made the hole. Only 1.8% of these were occupied by any bee or wasp species. In contrast to the natural wood objects, artificial nests had high occupancy ( c . 30%). Hole diameter, rather than tree species, hole type or stand age, was the most important factor explaining occupancy of a certain aculeate species. Holes in standing dead wood (SDW) had higher occupancy than holes in stumps and logs. The results are discussed in the context of aculeate life history traits. It is argued that the reason for the low occupancy in the natural dead wood, especially in the stumps, was that most holes were situated in moist and decayed wood, and offered inferior conditions for offspring during the development from egg to adult. Retention and creation of SDW objects of different tree species at final felling is recommended.